Rancang Bangun Sistem Informasi Untuk Memeriksa Ketersediaan Stok Barang Berbasis Web (Studi Kasus Warunk Oey) - Renaldi; Maulana Fansyuri (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
Inventory system is a system to find out the stock of goods in a store or a warehouse. Inventory systems have been widely used by business actors with various technologies. With a goods inventory system, the owner or officer can check the available inventory, incoming goods data, and outgoing goods data. The author designed a web-based stock inventory system at Warunk Oey as a case study in writing this thesis. Warunk Oey was established in 2019. The establishment of this coffee shop was due to encouragement from the owner to open business opportunities for the community, and the enthusiasm of young people who often gather in places that provide food or drinks, so the owner took advantage of this opportunity to establish this coffee shop business. Warunk Oey does not yet have a stock inventory system, so to record data for stock items is still done manually. With the design of this web-based inventory system, it is hoped that it can help the officers who work at Warunk Oey in collecting inventory data and can record incoming and outgoing goods better than before which was still done manually.